O significado da violência para jovens de classe média autores de ato infracional - Oliveira, Maristhela Bergamim de (2008)
The well-known increase of violence performed by middle-class teenagers which is exposed by means of communication goes against the exiguity of academic studies related to this group. The analyses are predominantly centered in poor territories. This work has performed a violence analysis through the meaning which middleclass teenagers, authors of infraction acts contribute to the phenomenon. The extension of violence concept relies on the analysis of its true sources anchored in the capitalist society and in the political- economic and social- cultural changes resulted from the globalization which forms a new way of sociability ruled in the individualism and emptiness of otherness. Through a qualitative approach which uses the content analysis of semi-structured interviews as a technique of data analyses, the empirical interview was performed with 7 middle-class teenagers between 16 and 21 years who fulfilled social-educative measures in the open air (Supervised Freedom and Community Service) along with the children and teenagers jurisdiction in Vitória – ES. The collected content analysis was performed under four themes: youth; family; study, work, project for the future and violence. In the complementarity among the themes, the current brightening mediation of violence meaning was addressed. Studying violence as an objective and subjective expression not only performed by low-class teenagers but also by middle-class ones, we have notice characteristics of their juvenile condition which make them unified and exposed to the historical conflicts appeared in the contemporary society. On the other hand, the study shows that the class condition of the young reflects in an emphatic and distinctly way in the outline of their social position. In the face of people’s disregard, the privatization of family solutions in the distinct resources and capacities will define and consolidate its course.